Alloying Behavior of Self‐Assembled Noble Metal Nanoparticles. Issue 38 (29th June 2016) - Kühn, Laura; Herrmann, Anne‐Kristin; Rutkowski, Bogdan; Oezaslan, Mehtap; Nachtegaal, Maarten; Klose, Markus; Giebeler, Lars; Gaponik, Nikolai; Eckert, Jürgen; Schmidt, Thomas J.; Czyrska‐Filemonowicz, Aleksandra; Eychmüller, Alexander
Abstract: The atomic redistribution processes occurring in multiparticle nanostructures are hardly understood. To obtain a more detailed insight, we applied high‐resolution microscopic, diffraction and spectroscopic characterization techniques to investigate the fine structure and elemental distribution of various bimetallic aerogels with 1:1 compositions, prepared by self‐assembly of single monometallic nanoparticles. The system Au–Ag exhibited a complete alloy formation, whereas Pt–Pd aerogels formed a Pd‐based network with embedded Pt particles. The assembly of Au and Pd nanoparticles resulted in a Pd‐shell formation around the Au particles. This work confirms that bimetallic aerogels are subject to reorganization processes during their gel formation. Abstract : Mix and match : The alloying behavior of Au–Ag, Pt–Pd, and Au–Pd 1:1 bimetallic aerogels was investigated by high‐resolution microscopic, diffraction, and spectroscopic techniques. Unexpected elemental distributions were observed that demonstrate the strong dependence on the kinetic energy introduced into the system by nanoparticle collision during the gel formation.